Ambident reactivity of enolizable 5-mercapto-1H-tetrazoles in trapping reactions with in situ-generated thiocarbonyl S-methanides derived from sterically crowded cycloaliphatic thioketones - Grzegorz Mlostoń; Małgorzata Celeda; Marcin Palusiak; Heinz Heimgartner; Marta Denel-Bobrowska; Agnieszka B. Olejniczak (Beilstein Journal of Organic Chemistry)
The in situ-generated thiocarbonyl S-methanides (thiocarbonyl ylides), derived from cycloaliphatic thioketones, are efficiently trapped by enolizable 1-substitued 5-mercapto-1H-tetrazoles and formation of the corresponding N–H or S–H insertion products, i.e., thioaminals or dithioacetals, respectively, was observed. In some instances, both products were formed side by side and could be separated by chromatography. Two novel, sterically overcrowded bis-spiro(cyclopentyl) and bis-spiro(cyclohexyl)-substituted thiocarbonyl S-methanides were thermally generated from the corresponding 1,3,4-thiadiazolines and their reactivity towards 5-mercapto-1H-tetrazoles was compared with well-known analogues derived from adamantanethione and 2,2,4,4-tetramethyl-3-thioxocyclobutanone. Some of the isolated thioaminals were observed to undergo thermal isomerization in CDCl3 solution yielding the corresponding dithioacetals. Structural analysis of the isolated products of S–H and N–H insertion was carried out based on spectroscopic data (1H and 13C NMR) and the structures of two representatives were established by using the X-ray single crystal diffraction analysis method. Biological activity (cytotoxicity) of some selected products derived from 5-mercapto-1H-tetrazoles was also examined.